A highly stabilized single crystalline nickel-rich LiNi0.8Co0.1Mn0.1O2 cathode through a novel surface spinel-phase modification. (1st May 2020) - Chen, Xi; Tang, Yu; Fan, Changling; Han, Shaochang
Abstract: For developing high-energy-density nickel-rich layered oxide cathodes with extended cycle life and rate capability, it is necessary to mitigate mechanical degradation caused by volume change and surface side reactions between cathode and electrolyte. To overcome these problems, a novel single crystalline LiNi0.8 Co0.1 Mn0.1 O2 material is coated by Li-reactive materials. Results show that the degree of cation mixing is significantly reduced and it is caused by the coating layer. The residual lithium compounds on the surface of the material are greatly removed by the coating materials through the formation of spinel Co3 O4 and LiMn2 O4 layer. The electrochemical performance of the modified materials is significantly improved. They conserve 91.4% and about 89.9% of the initial capacity (186.6 mAh·g −1 and 186.5 mAh·g −1, respectively) at 1 C after 100 cycles. They also exhibit greater rate capability of 161.7 mAh·g −1 and 157.9 mAh·g −1 at 5 C, remaining 79.3% and 77.4% capacity of 0.1C. The enhancements are attributed to the coated spinel phase with excellent structural stability. This generated cubic spinel phase suppresses volume change and thus inhibits the formation of surface cracks, resulting in fine surface structure during charge and discharge process.